Polypedates smaragdinus Blyth, 1852—a senior subjective synonym of Rhacophorus maximus Günther, 1858 - Ohler, Annemarie; Deuti, Kaushik (Zootaxa, 2018)
After more than 160 years, the onomatophores (name-bearing types) of Polypedates smaragdinus Blyth, 1852 were located in the collection of the ZSI (Kolkata, India). This allowed to study the specimens, to identify them and to propose an allocation of this nomen to the taxon Rhacophorus maximus. To stabilize nomenclatural and taxonomic issues, a lectophoront (lectotype) is designated for Polypedates smaragdinus Blyth, 1852 and described. A formal synonymy list is given. The species currently known as Rhacophorus maximus Günther, 1864 should now bear the nomen Rhacophorus smaragdinus (Blyth, 1852).